INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI PEMBIASAAN DAN KETELADANAN DALAM PEMBELAJARAN ONLINE - RINI FAJRIYAH; BAKHRUDDIN FANNANI; MUHAMMAD AMIN NUR (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
Religious education is the basic foundation of society. In internalizing the values of Islamic religious education, habituation and example are needed. However, due to the Covid-19 pandemic, the government recommends that learning activities be carried out online to stop the spread of covid-19. The interaction between teachers and students is limited so that all parties are required to be able to think creatively, innovatively and technologically literate in developing learning so that children's education continues to develop well despite all the limitations. This study to analyze the values of PAI which are internalized in online learning and the process of internalizing PAI values through habituation and example in online learning at SDIT Al-Uswah Singosari. The approach used is a qualitative approach with the type of case study research. Data collection techniques using observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation and drawing conclusions. The results of the study show that: 1) PAI values that are internalized in online learning are Divine values and Insaniyah values. 2) The process of internalizing PAI values through habituation and example in online learning is carried out using three stages, namely value transformation, value transactions and value transinternalization.